2020
DOI: 10.1111/coa.13494
|View full text |Cite
|
Sign up to set email alerts
|

The effect of three‐dimensional visualisation on performance in endoscopic sinus surgery: A clinical training study using surgical navigation for movement analysis in a randomised crossover design

Abstract: Objectives Endoscopic imaging techniques and endoscopic endonasal surgery (EES) expertise have evolved rapidly. Only few studies have assessed the effect of three‐dimensional (3D) endoscopy on endoscopic sinus surgery (ESS). The present study aimed to objectively and subjectively assess the additional value of 3D high‐definition (HD) endoscopy in ESS. Design A randomized crossover study of endoscopic surgery performance, using five ESS tasks of varying complexity, performed on Thiel embalmed human specimens. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…As such, these studies were classified as prospective randomized crossover trials. The tasks being used varied between studies, with the majority of studies reporting outcomes of multiple tasks; for example Ten Dam et al 21 assessed five different tasks with both endoscopes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As such, these studies were classified as prospective randomized crossover trials. The tasks being used varied between studies, with the majority of studies reporting outcomes of multiple tasks; for example Ten Dam et al 21 assessed five different tasks with both endoscopes.…”
Section: Resultsmentioning
confidence: 99%
“…For the remaining aspects, the risk of bias was generally low, with the exception of selection and detection bias in Albrecht et al 22 The risk of bias for Ogino‐Nishimura et al 19 and Tabaee et al 25 was assessed differently to the other studies, as these were nonrandomized case series. No studies reported receiving funding, although Ten Dam et al 21 stated that they received nonfinancial support.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endoscopic-assisted endonasal surgery has been increasingly employed over the past two decades, and its development was mainly focused on providing better optics and improved instruments and accelerating the learning curve of young surgeons. In terms of visualization technologies, high-resolution image acquisition and 3D technology applied to the endoscopic vision have been developed [27,29]. Furthermore, in order to enhance the orientation during surgery the combination of navigation together with endoscopy is established; however, being limited to pointer navigation functionality during surgery.…”
Section: Discussionmentioning
confidence: 99%